Penerapan Alat Bantu Lifter Bridge Untuk Mengurangi Waktu dan Jarak Tempuh Dalam Pemindahan Barang Setengah Jadi di PT. TMMIN - Yulvani Anggi Rahmawati (Jurnal Teknika, 2021)
PT TMMIN's logistics department is responsible for the smooth supply of component parts to the production line. In the delivery of parts, there is a problem, namely traffic disturbances in the PAD supply with the supply ip module. Both supplies cannot be in the same area due to insufficient area space. This situation causes the operator's workload to be a waste of steps and time. To overcome this problem, it is proposed to replace the part delivery tool that is currently used with a push dolly with a karakuri lifter bridge. Tool changes are carried out with 3M+1E aspects, namely method, material, man and environment. Change of equipment can affect factors such as no traffic disruptions with other supplies, reduction of SPS area, reduction of SPS distance to pp module and increasing company productivity efficiency.